Konsep Kebebasan Kehendak Manusia Sebagai Penentu Hidup Sosial: Studi Analisis Pemikiran Friedrich Nietzsche - Hasan Abdul Wafi; Umi Wasilatul Firdausiyah (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2022)
The discourse of this research leads to social life, which in Friedrich Nietzsche's perspective is determined from the concept of freedom of human will. The purpose of this research is to examine how the concept of the free will of humans in Friedrich Nietzsche's perspective can be a determinant of human social life itself. The research method used by the author is in the form of philosophical hermeneutics, the type of data collection is documentation, and the data analysis is descriptive-philosophical. The results of this study are in the form of a benchmark for human life that depends on the freedom of human will, with Nietzsche's explanation that human life has a responsive structure that is hidden in the concept of freedom of will. This is what Nietzsche means in the influence of the support of human life. So that human social life will not be separated from human action and will, which is witnessed by consciousness, this also reflects the freedom of human will. In essence, the concept of freedom referred to by Nietzsche has the mission of forming human social life, both in terms of interaction and responsibility for humans themselves.